1982
DOI: 10.1002/jat.2550020510
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term toxicological studies with impromidine (SK&F 92676): A specific histamine H2‐receptor agonist

Abstract: Impromidine is a specific, potent histamine H2-receptor agonist. The present paper describes the results of acute and short-term repeated-dose toxicity studies with impromidine in rodents and dogs. The intravenous LD50 was 9.6 mg kg-1 in male mice, 12.7 mg kg-1 in female mice and 25.5 mg kg-1 in rats. The minimum lethal dose in dogs after 30 min intravenous infusion was 27.7 mg kg-1 during the infusion and 4 mg kg-1 within 14 days. In 12- or 14-day tests in rats by the intravenous (maximum dose 3.24 mg per kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…A recent study with impromidine (H2R-agonist) in rats and dogs demonstrated that impromidine had no serious toxicological effects at lower dose. However, in dogs, at the higher doses minor pathological changes were seen in liver (Lesli et al, 1982).…”
Section: Introductionmentioning
confidence: 90%
“…A recent study with impromidine (H2R-agonist) in rats and dogs demonstrated that impromidine had no serious toxicological effects at lower dose. However, in dogs, at the higher doses minor pathological changes were seen in liver (Lesli et al, 1982).…”
Section: Introductionmentioning
confidence: 90%